Gene Cascade Shift and Pathway Enrichment in Rat Kidney Induced by Acarbose Through Comparative Analysis - Weng, Chun-Yue; Zhu, Mo-Han; Dai, Ke-Lei; Mi, Zhe-Yan; Wang, Yuan-Shan; Liu, Zhi-Qiang; Zheng, Yu-Guo (Frontiers in Bioengineering and Biotechnology, 2021)
Acarbose is an effective anti-diabetic drug to treat type 2 diabetes mellitus (T2DM), a chronic degenerative metabolic disease caused by insulin resistance. The beneficial effects of acarbose on blood sugar control in T2DM patients have been confirmed by many studies. However, the effect of acarbose on patient kidney has yet to be fully elucidated. In this study, we report in detail the gene expression cascade shift, pathway and module enrichment, and interrelation network in acarbose-treated Rattus norvegicus kidneys based on the in-depth analysis of the GSE59913 microarray dataset. The significantly differentially expressed genes (DEGs) in the kidneys of acarbose-treated rats were initially screened out by comparative analysis. The enriched pathways for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were further identified. The protein-protein interaction (PPI) analysis for DEGs was achieved through the STRING database mining. Pathway interrelation and hub genes for enriched pathways were further examined to uncover key biological effects of acarbose. Our results revealed 44 significantly upregulated genes and 86 significantly downregulated genes (130 significant differential genes in total) in acarbose-treated rat kidneys. Lipid metabolism pathways were considerably improved by acarbose, and the physical conditions in chronic kidney disease (CKD) patients were improved possibly through increase of the level of high-density lipoprotein (HDL) by lecithin-cholesterol acyl-transferase (LCAT). These findings suggested that acarbose may serve as an ideal drug for CKD patients, since it not only protects the kidney, but also may improve the complications caused by CKD.